The impact of probiotic supplementation on metabolic health in healthy women of reproductive age: a systematic review. Issue 12 (11th November 2020) - Byrne, David F.; Geraghty, Aisling A.; Yelverton, Cara A.; Murphy, Eileen F.; Van Sinderen, Douwe; Cotter, Paul D.; McAuliffe, Fionnuala M.
Abstract : Products containing probiotics are targeted at healthy or at-risk individuals as a preventative measure to minimise disease risk. Abstract : Products containing probiotics are targeted at healthy or at-risk individuals as a preventative measure to minimise disease risk. Most studies assessing the efficacy of probiotics in humans include a mixture of healthy and unhealthy populations, while studies that focus solely on female populations are largely limited to pregnancy or those with health conditions. Pre-conception is a significant time-point during the life-course, and improving female health status during this period may positively influence future offspring. The objective of this review is to assess the effect of probiotics administered in oral capsule formulation, on metabolic and immune markers in healthy, non-pregnant women of reproductive age. This review followed the PRISMA guidelines. Pubmed, EMBASE, CINAHL, and Web of Science were searched for relevant studies. English language articles relating to randomised-controlled trials were included. The search returned 3250 publications after duplicates were removed. Title (2516), abstract (642), and full text (87) screening excluded 3993 studies from consideration. Five papers were identified with outcomes of interest, and analysis of these showed no conclusive evidence that probiotic capsule supplementation elicited positive effects in this healthy population. This study highlights the need for further research to investigate the role that probiotics play during the pre-conception period, on female metabolic and immune health.